PENGGUNAAN BIOCHAR DIPERKAYA NITROGEN PADA TANAMAN JAGUNG - Titik Islami (BUANA SAINS, 2019)
Most agricultural land in lndonesia has a low organic matter content, and this is due to the fast decomposition rate of soil organic matter. The rapid decomposition of soil organic matter causes low soil fertility. To maintain high agricultural yields, it is necessary to add soil organic matter repeatedly in each planting season with a high dose ( 10 tons / ha). Farmers considered that the addition of high-dose organic matter to their agricultural land is not economical and difficult to do. Therefore, soil organic matters which is resistant to decomposition is needed, so that it can last longer in the soil. One of the recalcitrant soil organic matter is biochar, and many studies have shown that biochar can reduce the need for nitrogen in the next cropping season. Previous research has shown that biochar can be enriched with nitrogen as an organic fertilizer. This study aims to study the effect of biochar which has enriched nitrogen from ammonium on the growth and yield of maize. The study was conducted in Landungsari Village, Malang City in July to December 2018. This study used a randomized block design (RBD) with combinations of 5 treatments and 5 replications. The treatments in this study were: B0 (control); B1 (nitrogen fertilizer 90 kg / ha); B2 (nitrogen fertilizer 90 kg / ha + biochar); B3 (biochar enriched with ammonium sulfate 4 tons / ha); B4 (manure 4 tons / ha + nitrogen f'ertilizer 90 kg / ha). The results of the study showed that biochar enriched with ammonium sulfate at a dose of 4 tons / ha increased the growth and yield of maize. Biochar enriched with ammonium sulfate shows the ability to hold nitrogen which can then be released in the soil in the form of NH4 + to be absorbed by plants.